HUBUNGAN HYGIENE DAN SANITASI LINGKUNGAN DENGAN KEJADIAN STUNTING PADA BALITA DI WILAYAH PUSKESMAS DADOK TUNGGUL HITAM TAHUN 2021 - Laura Zeffira; Tati Khairina; Hidayaturrahmi, Hidayaturrahmi; Zukhri Zainun; Andri Prastian Utama (Yayasan Nusantara Hasana Berdikari, 2023)
Stunting is a chronic nutritional problem in toddlers characterized by the height of children who are shorter than children of the same age. Stunting in children is a serious problem, because it is associated with the risk of greater morbidity and mortality, obesity and non-communicable diseases in the future, short adults, poor cognitive development, and low productivity and income. The aim of the study to determine the relationship between hygiene and environmental sanitation with the incidence of stunting in toddlers in the Dadok Tunggul Hitam Community Health Center in 2021. Methods using a correlative analytic study with a cross-sectional approach. The sample was selected using a total sampling technique of 55 toddlers representing all toddlers recorded at the Dadok Tunggul Hitam Puskesmas, Koto Tangah District, Padang City in 2021. This research was conducted from April 2020 to February 2021. Univariate data analysis was presented in the form of frequency and percentage distributions and bivariate analysis using the chi-square test and data processing using the computerized SPSS version 16.0 program. The most toddlers in the Dadok Tunggul Hitam Puskesmas area in 2021 aged> 36 months were 27 people (49.1%), the most under-five in the Dadok Tunggul Hitam Puskesmas area in 2021 were female 30 people (54.5%), more than half of toddlers in the Dadok Tunggul Hitam Health Center Area in 2021 did not experience stunting, namely 42 people (76.4%), more than half of children under five in the Dadok Tunggul Hitam Health Center Area in 2021 has a status of healthy environmental hygiene and sanitation, namely 37 people (67.3%), and there is a relationship between hygiene and environmental sanitation with the incidence of stunting in children under five in the Dadok Tunggul Hitam Community Health Center in 2021 (p = 0.000). It is proven that there is a relationship between hygiene and environmental sanitation with the incidence of stunting in children under five in the Dadok Tunggul Hitam Community Health Center in 2021.